دور اعادة التأمين في تغطية الاخطار الكوارثية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The re-insurance of    the same important   role in the development programs and activities that reinsurance  companies   and   their   level    of development and the mechanisms of action and the laws that govern the relationship between the re-insurance companies and direct companies reflect the cultural level and degree of progress of any country.                                                               As well as natural that philosophy Reinsurance reflect the    extent of the security    risks that are located,     whether f0   money or to persons  or property in accordance with the contractual terms of parallel   .                                                               Given the importance of re-insurance sector and the need to   develop the   level    of      his performance came this research to identify the nature of the activity reinsurance   companies.                                                  So came the goal of research in the study of the reality of reinsurance and the search for ways to help in activating the role of insurance and to minimize the negative effects of the disaster was search has included a review of previous studies and research that dealt with reinsurance risks catastrophic were also reviewed in the entrance and in detail (to re-secure the dangers catastrophic) in terms of importance and the concept of evolution as well as the nature of disasters and their causes and effects  .